2005
DOI: 10.1080/02791072.2005.10399749
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sense of Coherence and Attribution of Responsibility for Problems and Their Solutions, and Cessation of Substance Abuse Over Time

Abstract: The present study deals with personal and psychological characteristics of addicts coping with abstinence from drugs in various stages of recovery. The study focuses primarily on two personal variables: attribution of responsibility for the problem and its solution, and the sense of coherence. Additional factors that were examined in the study are demographic variables, which include those related to drug addiction. The sample included 128 short-term abstinent patients in the early stages of recovery after det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Feigin and Sapir (2005) found that SOC scores were signifi cantly higher among 40 former heroin addicts and polydrug abusers who stopped drug abuse for a period of between two to eight years compared with 128 short-term abstinent patients in the early stages of recovery after detoxification. Chen's (2006) cross-sectional study examined the differ ences in SOC scores among Israeli prisoners recovering from drug and alcohol addiction over various time periods and fo und higher SOC scores in subjects who were abstinent for six to 24 months compared to scores of those who were abstinent for six months or less.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Feigin and Sapir (2005) found that SOC scores were signifi cantly higher among 40 former heroin addicts and polydrug abusers who stopped drug abuse for a period of between two to eight years compared with 128 short-term abstinent patients in the early stages of recovery after detoxification. Chen's (2006) cross-sectional study examined the differ ences in SOC scores among Israeli prisoners recovering from drug and alcohol addiction over various time periods and fo und higher SOC scores in subjects who were abstinent for six to 24 months compared to scores of those who were abstinent for six months or less.…”
Section: Discussionmentioning
confidence: 97%
“…The characteristic of stability may provide important information about whether SOC is a deep-rooted personality trait that can indicate improved chances for sustained drug abstention, or if SOC is more closely related to specific and transient states and, as such, needs to be reinforced over time for continued therapeutic success (Feigin & Sapir 2005). The aims of the current longitudinal prospective study were to assess the role of SOC in predicting successful outcomes for former heroin addicts in the setting of MMT and to determine whether SOC is a stable parameter over time or one dependent upon given circumstances.…”
Section: Sense Of Coherence and Mmtmentioning
confidence: 99%
See 1 more Smart Citation
“…The few studies that have been conducted concerning the impact of the sense of coherence in substance-dependent populations have generally yielded relatively strong relationships between higher sense of coherence and improvement in substance use problems [13,14], or lower mortality rates during follow-up [15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…Bengtsson‐Tops & Hansson, 2001; Carstens & Spangenberg, 1997; Cederblad & Hansson, 1996; Eklund, Hansson & Bengtsson‐Tops, 2004; Johnson, 2004; Volanen, Lahelma, Silventoinen & Suominen, 2004; Volanen, Suominen, Lahelma, Koskenvuo & Silventoinen, 2006, 2007; Wolff & Ratner, 1999). In summary, Feigin & Sapir’s (2005, p. 63) literature review found that “the concept of SOC has a broad theoretical base and a growing and impressive body of empirical evidence supporting its utility”.…”
Section: Introductionmentioning
confidence: 99%